A 2-month-old boy with hemolytic anemia and reticulocytopenia following intravenous immunoglobulin therapy for Kawasaki disease: a case report and literature review - Kim, Na Yeon; Kim, Joon Hwan; Park, Jin Suk; Kim, Soo Hyun; Cho, Yeon Kyung; Cha, Dong Hyun; Kim, Ki Eun; Kang, Myung Suh; Lim, Kyung Ah; Sheen, Youn Ho (Clinical and experimental pediatrics, 2016)
Herein, we report a rare case of hemolytic anemia with reticulocytopenia following intravenous immunoglobulin therapy in a young infant treated for Kawasaki disease. A 2-month-old boy presented with fever lasting 3 days, conjunctival injection, strawberry tongue, erythematous edema of the hands, and macular rash, symptoms and signs suggestive of incomplete Kawasaki disease. His fever resolved 8 days after treatment with aspirin and high dose infusion of intravenous immunoglobulin. The hemoglobin and hematocrit decreased from 9.7 g/dL and 27.1% to 7.4 g/dL and 21.3%, respectively. The patient had normocytic hypochromic anemia with anisocytosis, poikilocytosis, immature neutrophils, and nucleated red blood cells. The direct antiglobulin test result was positive, and the reticulocyte count was 1.39%. The patient had an uneventful recovery. However, reticulocytopenia persisted 1 month after discharge.